2012
DOI: 10.1152/jn.00356.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying rule learning-induced enhancement of excitatory and inhibitory synaptic transmission

Abstract: Saar D, Reuveni I, Barkai E. Mechanisms underlying rule learning-induced enhancement of excitatory and inhibitory synaptic transmission. J Neurophysiol 107: 1222-1229, 2012. First published November 30, 2011 doi:10.1152/jn.00356.2011.-Training rats to perform rapidly and efficiently in an olfactory discrimination task results in robust enhancement of excitatory and inhibitory synaptic connectivity in the rat piriform cortex, which is maintained for days after training. To explore the mechanisms by which such s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
79
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 44 publications
18
79
1
Order By: Relevance
“…Such enhanced GABA release was not observed in our present and previous (Saar et al 2012) studies. Notably, such enhanced release is attributed to decrease in the small conductance channel-mediated potassium current which affects repetitive spike firing.…”
Section: Learning-induced Modulation Of Gaba B -Dependent Postsynapticontrasting
confidence: 78%
See 3 more Smart Citations
“…Such enhanced GABA release was not observed in our present and previous (Saar et al 2012) studies. Notably, such enhanced release is attributed to decrease in the small conductance channel-mediated potassium current which affects repetitive spike firing.…”
Section: Learning-induced Modulation Of Gaba B -Dependent Postsynapticontrasting
confidence: 78%
“…Our laboratory has previously shown that OD learning is accompanied by enhancement in intrinsic neuronal excitability, excitatory synaptic transmission, and GABA A -mediated fast inhibitory synaptic transmission, throughout the piriform cortex pyramidal cell population (Brosh and Barkai 2009;Saar et al 1998Saar et al , 2002Saar et al , 2012. While activity-induced enhancement in GABA A -mediated inhibitory synaptic transmission has been shown in several brain regions of the mammalian brain (Grunze et al 1996;Holmgren and Zilberter 2001;Komatsu and Yoshimura 2000), plasticity of the GABA B -mediated synaptic inhibition has been less studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats trained in a particularly difficult olfactory discrimination (OD) task demonstrate a dramatic increase in their capability to acquire memories of new odors, termed "rule learning," or "learning set" (Saar et al 1998;Slotnick et al 2000). At the cellular level, rule learning results in a global change in the 3 components controlling the intrinsic PC circuit: intrinsic neuronal excitability (Saar et al 1998;Saar and Barkai 2009), excitatory synaptic inputs (Saar et al 1999(Saar et al , 2002(Saar et al , 2012Knafo et al 2001Knafo et al , 2005Cohen et al 2008), and synaptic inhibition (Brosh and Barkai 2009;Saar et al 2012). These modifications have 2 major common traits:…”
Section: Introductionmentioning
confidence: 99%